PERAN WAKA HUMAS DALAM UPAYA PROMOSI GUNA MENARIK MINAT CALON PESERTA DIDIK DI MTs AL-AMIRIYYAH BLOKAGUNG BANYUWANGI - Khaudli, Muhammad Imam; Dimyati, Muh; Farizi, Ahmad Kanzul (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2022)
The purpose of this study is to determine the role of public relations waka in promotional efforts to attract prospective students in MTs Al-Amiriyyah. Public relation is an effort to foster public participation so that it can foster public trust or the public, interested in registering their sons and daughters in MTs Al-Amiriyyah. The role of public relations is very important in improving the quality of an educational institution because public relations as a communicator between the community and schools so that public relations can accommodate community aspirations related to all activities in an educational institution so that it can grow the image of an educational institution in the eyes of the community. This type of research is a qualitative method approach, namely by using a descriptive approach with interview observation and documentation of problems in this study, researchers try to answer three questions contained in MTs Al-Amiriyyah, namely: (1). What is the role of Public Relations in the promotion and marketing process in order to attract the interest of prospective students, (2). What has been done by WAKA Humas in promotion so that prospective students are interested in entering MTs Al-Amiriyyah. Bet based on the findings obtained by the researcher, that for Waka Humas at MTs Al Amiriyyah about strategies or promotions that can be done by Waka Humas in a Promotion in an effort to attract the interest of prospective students, namely as follows: (1). Through the PPL teaching program for superior classes to SD /MI in the Banyuwangi area as a means of Promoting MTs Al Amiriyyah. (2) Carry out promotions through online social media such as Websites, Whatsapp, Facebook, Instagram, and Youtube. Providing information services and the latest developments around Madrasah to parents so as to make it easier for parents to find out the quality of education in MTs Al Amiriyyah.